Observation on the uses of Mobile Phones to Support Informal Learning - Othman, Mohd Azlishah (International Journal of Interactive Mobile Technologies (iJIM), 2012)
This paper explores how a group of undergraduate students in one of the university in South of Malaysian use their mobile phones to perform informal learning activities related to the content of their courses outside the classroom. The paper also addresses the usefulness of informal learning activities to support studentsâ?? learning. The study adopts an exploratory case study design and uses two methods of data collection including questionnaires and interviews. Main findings suggest that students performed informal learning activities mostly from office, home, interacting mainly with classmates. It also shows that students were in control of their informal learning activities without tutor or SMEsâ?? input. However, it was found that students used only a limited number of applications but these were considered useful to their learning. The paper contributes to a discussion of the implications of training and instructional support to help students to take more advantage of mobile phone applications to support informal learning. The conclusion is discussed about the further research in this domain.